FAKTOR FAKTOR YANG BERHUBUNGAN DENGAN PENYAKIT DEMAM CHIKUNGUNYA DI WILAYAH KERJA PUSKESMAS GANDAPURA KABUPATEN BIREUEN TAHUN 2019 - aris winandar (Jurnal Maternitas Kebidanan, 2019)
In 2012 in the District Gandapura number of Chikungunya cases there were 37 cases. Suspect cases are found in the village cikungunya tupin Siron 12 cases, a total of 18 cases airy Timu diiikuti Cot jabet 7 cases and larvae-free rate is the lowest of the epidemiological investigation was 5% ahead Teupin Siron. The purpose of this study was to determine the factors associated with Chikungunya fever in the Work Area Health Center Gandapura bireuen District in 2019. This type of study is a cross sectional analytic. The population in this study is the head of a family with a number of 72 samples. This research has been conducted on tada 18 s / d 28 Januari in 2019. The results showed no significant association between the presence of water with events Shelter p.value value = 0.023, there was no significant association between napping habits with incidence of chikungunya with p.value value = 0.486, there was no significant association between habitual drain water reservoir with an incidence of chikungunya with p.value value = 0.716, there was no significant association between the habit of closing the water reservoir with the incidence of chikungunya with p.value value = 0.153, there was no significant association between the occurrence bury thrift chikungunya with value p.value = 0.153, there was no significant association between the incidence of chikungunya room temperature with p.value value = 0.128. Based on these results it is expected that researchers advice to people working area Gandapura Bireuen to always maintain the cleanliness and immediately report to the health worker if there are people who terindefikasi chikungunya.